REVIEW – PERKEMBANGAN VIRUS ZIKA - Rizky Ramadhan Maulana; Irma Antasionasti; Fatimawali Fatimwali; Trina Tallei (UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACTZika virus (ZIKV) is a virus of the genus Flavivirus (family Flaviviridae) that is capable of infecting humans. This virus poses a risk to human health. The main vector for the spread of ZIKV is the bite of the Aedes aegypti and Aedes albopictus mosquitoes. To date, there is no approved specific treatment for ZIKV infection, the recommended therapy is supportive to treat symptoms. Vaccine development continues to be carried out as a concrete step to overcome the global spread of the virus. This article discusses the genome structure, epidemiology, viral transmission, clinical manifestations, vaccine development, and prevention and treatment of ZIKV infection. Keywords: Zika Virus, Epidemiology, Transmission, Vaccines. ABSTRAKVirus Zika (ZIKV) merupakan virus dari genus Flavivirus (famili Flaviviridae) yang mampu menginfeksi manusia. Virus Zika dapat menjadi ancaman bagi kesehatan manusia.Vektor utama penyebaran ZIKV adalah gigitan nyamuk Aedes aegypti dan Aedes albopictus. Sampai saat ini, belum ada pengobatan spesifik yang disetujui untuk infeksi ZIKV, terapi yang dianjurkan bersifat suportif untuk mengobati gejala.Pengembangan vaksin terus dilakukan sebagai langkah kongkrit untuk mengatasi penyebaran virussecara global.Artikel ini membahas mengenai struktur genom, epidemiologi, transmisi virus, manifestasi klinis, pengembangan vaksin serta pencegahan dan pengobatan dari infeksi ZIKV. Kata Kunci: Virus Zika, Epidemiologi, Transmisi, Vaksin